تمكين الشباب وأثره في نهضة الأمة الإسلامية : دراسة تطبيقية من السيرة النبوية - روبي، أسماء علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The Muslim Ummah is a resilient one and will prevail, inevitably, before the day of resurrection. But every ummah has its ups and downs and the Muslim ummah is currently awaits a revival of a new kind of generation. That generation is none other than the Muslim youth. The research discusses the revival in question, definition of Umma, the process of empowerment and its obstacles. To expedite this inevitable revival, a plan is needed. That plan depends on following the example of the Prophet's concept of nationhood. It is based on the leader who empowers the youth and comprehends their characteristics in order to create leaders who enlighten the world. The researcher applied the inductive and analytical approach to write this research. The most significant results that the writer found is that the human factor is the core of a nation's revival and its youth is the most important asset. Therefore, focusing on the youth and empowering them will help accomplish the revival. The greatness of Prophet Muhammad (PBUH) was that he was able to harness and nurture the potential of young and new nation.